2023
DOI: 10.3390/molecules28031390
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling and Potential Taste Biomarkers of Two Rambutans during Maturation

Abstract: The metabolite-caused taste variation during rambutan maturation is unknown due to a lack of systematic investigation of all components. In this study, three growing stages, including unripe (S1), half-ripe (S2), and full-ripe (S3) BY2 and BY7 rambutans were compared and profiled by UPLC–MS/MS-based widely targeted metabolomics analysis. We demonstrated that the sugar-acid ratios of two rambutans were greatly improved between the S2 and S3 stages. A total of 821 metabolites were identified, including 232, 205,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…To eliminate the effects of quantity on pattern recognition, we applied a log 2 transformation of peak areas for 46 DMs, followed by a correlational analysis between them and the taste indicators [ 33 ]. As shown in Figure 5 B, the target 46 DMs correlated strongly with 11 of the 27 taste indicators ( p < 0.05, Pearson’s r > 0.8), including one sugar, nine amino acids, one chlorogenic acid, and trigonelline ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To eliminate the effects of quantity on pattern recognition, we applied a log 2 transformation of peak areas for 46 DMs, followed by a correlational analysis between them and the taste indicators [ 33 ]. As shown in Figure 5 B, the target 46 DMs correlated strongly with 11 of the 27 taste indicators ( p < 0.05, Pearson’s r > 0.8), including one sugar, nine amino acids, one chlorogenic acid, and trigonelline ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the recent past, studies done by Chen et al 2019) have explored the metabolomics techniques for the estimation of fruits metabolites and their composition as affected by regional distributions and environmental stresses. For instance, Deng et al (2023) examined the alteration in the concentration of sugars, organic acids and AA in two different varieties of rambutan fruit during the maturation and ripening stage. They identified 20 metabolic pathways of which sugars metabolism and AA biosynthesis was the major one.…”
Section: Fruits Metabolomicsmentioning
confidence: 99%
“…Rambutan contained 3-O-p-coumaroylshikimic acid, which was observed to be the derivative of shikimic acid (shikimate) as well as precursor for the formation of aromatic AA, i.e., tyrosine, tryptophan and phenylalanine (Schmid & Amrhein, 1995). Deng et al (2023) identified D-fructose, fructose-6P and 3,4-digalloylshikimic acid as the precursors of shikimic acid. GC analysis of fatty aldehydes as dimethylacetal derivatives was the first recognition approaches for fatty aldehydes (Berdyshev, 2011).…”
Section: Fruit Flavour Volatile Compounds Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations